English as a Second Language teacher training practicum – exploring Polish university students’ experiences and perceptions – in search of supportive strategies - Dick-Bursztyn, Marta (Wydawnictwo Uniwersytetu Rzeszowskiego, 2024)
This study examines the experiences of Polish university students during their English as a Second Language (ESL) Teacher Training Practicum. By examining the challenges and transformations they undergo, we aim to understand their journey towards becoming educators. Beyond students’ reflections, we explore strategies to improve their practicum experiences. Using the Inventory of Experiences and Perceptions at Teaching Practice (IEPTP), we evaluate key aspects: learning and professional growth, socialisation in professional settings, socio-emotional facets, support and supervision, and vocational development. The research highlights shifts in perceptions, emphasising areas like vocational and professional development. It suggests strategies to enhance learning and support for student teachers, emphasising the crucial role of supervisors. The findings guide institutions in refining teacher training and ensuring students become adept ESL educators.

W artykule przeanalizowano doświadczenia studentów uniwersyteckich po odbytej praktyce nauczycielskiej z nauczania języka angielskiego. Badanie skupia się na wyzwaniach i zmianach, jakich doświadczają przyszli nauczyciele, oraz na strategiach wsparcia podczas praktyki. Wykorzystując kwestionariusz doświadczeń i postrzegania w praktyce nauczycielskiej (IEPTP), oceniono pięć kluczowych obszarów praktyki, takich jak nauka i rozwój, socjalizacja zawodowa, wsparcie oraz rozwój zawodowy. Wyniki ukazują znaczące zmiany w postrzeganiu praktykantów, zwłaszcza w obszarach rozwoju zawodowego i socjalizacji. Badanie wskazuje na istotność wsparcia opiekunów oraz proponuje strategie dla instytucji kształcących mające na celu optymalizację doświadczenia praktycznego i przygotowanie do bycia efektywnymi nauczycielami języka angielskiego.
Praktyka przedmiotowa studentów języka angielskiego jako drugiego – badanie doświadczeń i odczuć studentów/ praktykantów – w poszukiwaniu strategii wsparcia
Keywords: ESL teacher training practicum; learning and professional growth; IEPTP; support and supervision; kształcenie praktyczne nauczyciela anglisty; rozwój zawodowy; praktyka przedmiotowa; wsparcie i nadzór